Melatonin attenuates the TLR4-mediated inflammatory response through MyD88-and TRIF-dependent signaling pathways in an in vivo model of ovarian cancer - Chuffa, Luiz Gustavo de Almeida [UNESP] (2015)
Background: Toll-like receptors (TLRs) are effector molecules expressed on the surface of ovarian cancer (OC) cells, but the functions of the TLR2/TLR4 signaling pathways in these cells remain unclear. Melatonin (mel) acts as an anti-inflammatory factor and has been reported to modulate TLRs in some aggressive tumor cell types. Therefore, we investigated OC and the effect of long-term mel therapy on the signaling pathways mediated by TLR2 and TLR4 via myeloid differentiation factor 88 (MyD88) and toll-like receptor-associated activator of interferon (TRIF) in an ethanol-preferring rat model.Methods: To induce OC, the left ovary of animals either consuming 10% (v/v) ethanol or not was injected directly under the bursa with a single dose of 100 mu g of 7,12-dimethylbenz(a) anthracene (DMBA) dissolved in 10 mu L of sesame oil. The right ovaries were used as sham-surgery controls. After developing OC, half of the animals received i.p. injections of mel (200 mu g/100 g b.w./day) for 60 days.Results: Although mel therapy was unable to reduce TLR2 levels, it was able to suppress the OC-associated increase in the levels of the following proteins: TLR4, MyD88, nuclear factor kappa B (NFkB p65), inhibitor of NFkB alpha (IkB alpha), IkB kinase alpha (IKK-alpha), TNF receptor-associated factor 6 (TRAF6), TRIF, interferon regulatory factor 3 (IRF3), interferon beta (IFN-beta), tumor necrosis factor alpha (TNF-alpha), and interleukin (IL)-6. In addition, mel significantly attenuated the expression of IkB alpha, NFkB p65, TRIF and IRF-3, which are involved in TLR4-mediated signaling in OC during ethanol intake.Conclusion: Collectively, our results suggest that mel attenuates the TLR4-induced MyD88- and TRIF-dependent signaling pathways in ethanol-preferring rats with OC.